Improving Community Health, Economy and Food Security through the Cultivation of Tanaman Obat Keluarga (TOGA) the Community of Jambenenggang Village, Kebonpedes District (Group 8 Food Security Division) - Yepi Sopian; Ratih Fitria Siti Masrivah; Siti Julaeha; Siti Nuryanti; Suwarni; Seli Barokah (Indonesian Journal of Society Development, 2023)
This activity aims to describe to the community about improving health, economy and food security through the production of family medicinal plants (TOGA) in Jambenenggang Village, Kebonpedes District, Sukabumi Regency. Based on its geographical location, Jambenenggang village is a rural village so most of the people are farmers. In addition, Jambenenggang village has potential for development, one of which is the many plants used in family medicine. The method used in the implementation of this group 8 KKM service is socialization, training in making family medicines with plants grown in private yards. The result is that every family stays healthy, their body's immunity is maintained, they have land that can be cared for and utilized by the community so that it can help economic conditions and increase village food security